Experimental testing and numerical simulations of ship impact on axially loaded reinforced concrete piers. (March 2019) - Wan, Yunlei; Zhu, Lu; Fang, Hai; Liu, Weiqing; Mao, Yifeng
Highlights: A quasi-static compression test and the numerical simulation on the bow model was carried out. The static stiffness characteristic of the ship bow was compared with the dynamic ones. The impact force and the dynamic response of piers due to collision at different impact velocities with ships with different bow stiffnesses were experimentally studied. Three concrete materials were considered in modelling the pier to find the influence of different material model assumptions on the collision simulation. Finite element analysis of the full-scale ship-pier collision was conducted to examine the reasonability of the scaled model tests. A parametric analysis method was used to study the effects of the dynamic parameters and impact velocity on the impact force and ship bow crush depth. Abstract: Ship collision with bridge piers is one of the most frequent types of accidents that may lead to a bridge failure. The collision characteristic of bow structure is significant to the study ship-pier collision process. In this paper, the quasi-static compression test and numerical simulation of a simplified bow model were carried out to study the static stiffness characteristic of the ship bow for further comparison with the dynamic ones. To evaluate the performance of reinforced concrete (RC) piers against ship collision, and to guide the design of the bridge piers and anti-collision, scaled model tests of ship-pier collision and finite element simulations based on the main pier no. 217 of the Shijiu Lake Bridge were carried out. The damage process and failure mode of the pier were analysed. Instead of rigid or elastic materials in most of the previous works of numerical simulation of ship collision with bridge piers, the bridge pier is modelled with nonlinear materials to simulate the pier characteristics more accurately. To examine the reasonability of the scaled model tests, finite element analysis of the full-scale ship-pier collision was conducted. In the light of the numerical results, the design impact loads prescribed by Eurocode and AASHTO LRFD Bridge Design Specifications were evaluated. Parametric studies were carried out to investigate the effects of the dynamic parameters and impact velocity on the impact force and ship bow crush depth.